2003
DOI: 10.1149/1.1554916
|View full text |Cite
|
Sign up to set email alerts
|

NiCoFe Ternary Alloy Deposition

Abstract: The influence of Co 2ϩ and Fe 2ϩ bulk concentrations on the electrodeposition of NiCoFe ternary alloys is examined under conditions where the bulk concentration of Ni 2ϩ is in comparable excess. Experiments are carried out with recessed rotating cylinder cathodes at a single rotation rate. The Fe rate during alloy deposition appears independent of Co 2ϩ and Fe 2ϩ bulk concentrations but is enhanced compared to its single metal rate. Both catalytic and inhibiting effects are observed for Co deposition. The Co r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
4
23
0
Order By: Relevance
“…Electroanalytical studies of FeCoNi electrodeposits were performed by several researchers [23][24][25][26]. Phan et al demonstrated that their experimental data agreed well with the Hessami-Tobias model [23].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Electroanalytical studies of FeCoNi electrodeposits were performed by several researchers [23][24][25][26]. Phan et al demonstrated that their experimental data agreed well with the Hessami-Tobias model [23].…”
Section: Introductionmentioning
confidence: 91%
“…As a CoFe based ternary alloy, FeCoNi alloy is a widely investigated magnetic material [1,2,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Osaka group studied magnetic properties and other physical properties of electrodeposited FeCoNi alloys [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of Co to Ni can enhance the magnetic, hardness and wearresistance properties (Duch et al 2002;Zhuang and Podlaha 2003;Fan and Piron 1996;Bai and Hu 2002;Qiao et al 2006;Wang et al 2005). It would be an important issue to control the Co content of the Ni-Co alloy film codeposited in electrolyte for the desired property.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers reported the codeposition of Ni-Co films prepared in the simple chloride or sulfate (Fan and Piron 1996;Bai and Hu 2002) baths, or in the complex chlorideammonia hydroxide (Fan and Piron 1996) or chloridesulfate (Qiao et al 2006;Wang et al 2005) baths by adjusting the current density and cyclic voltages. When two or more elements were codeposited simultaneously, the effect of so-called anomalous codeposition behavior would appear (Zhuang and Podlaha 2003;Fan and Piron 1996;Wang et al 2005). That is, the composition of alloy deposits was different from that in electrolyte composition, which was related to the current density, temperature, pH, and other variables in electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…For a ternary alloy, an order of deposition preference can be deducted from the composition data of d.c. deposits. For iron-group metal alloys, this deposition preference is as follows: Fe>Co>Ni [34][35][36]. It is an open question how the order of the deposition preferences affects the composition evolution in the near-substrate zone.…”
Section: Composition Depth Profile Of Dc-plated Ternary Ni-co-fe Almentioning
confidence: 99%